1996
DOI: 10.1093/genetics/144.3.1053
|View full text |Cite
|
Sign up to set email alerts
|

Synonymous Substitutions in the Xdh Gene of Drosophila: Heterogeneous Distribution Along the Coding Region

Abstract: The Xdh (rosy) region of Drosophila subobscura has been sequenced and compared to the homologous region of D. pseudoobscura and D. melanogaster. Estimates of the numbers of synonymous substitutions per site (Ks) confirm that Xdh has a high synonymous substitution rate. The distributions of both nonsynonymous and synonymous substitutions along the coding region were found to be heterogeneous. Also, no relationship has been detected between Ks estimates and codon usage bias along the gene, in contrast with the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…309-310. f 2008 Cambridge University Press related to the HR effect at the gene and genomic level. For example, many studies have shown that rates of synonymous evolution increase with the length of coding sequence and levels of synonymous polymorphism are lower in genes with reduced codon bias (Comeron & Aguade, 1996;Moriyama & Powell, 1996;Comeron et al, 1999). Codon usage bias also decreases as the length of coding sequence increases (Moriyama & Powell, 1998;Comeron et al, 1999;Duret & Mouchiroud, 1999).…”
mentioning
confidence: 99%
“…309-310. f 2008 Cambridge University Press related to the HR effect at the gene and genomic level. For example, many studies have shown that rates of synonymous evolution increase with the length of coding sequence and levels of synonymous polymorphism are lower in genes with reduced codon bias (Comeron & Aguade, 1996;Moriyama & Powell, 1996;Comeron et al, 1999). Codon usage bias also decreases as the length of coding sequence increases (Moriyama & Powell, 1998;Comeron et al, 1999;Duret & Mouchiroud, 1999).…”
mentioning
confidence: 99%